Engineered bimetallic electrode materials for sustainable and selective electroreduction of CO2 into value-added products - Akshay Gandigawad; Hemavathi Manjunath; Chob Singh; Nitin K. Chaudhari; Hanimi Reddy Bapatu; Arvind H. Jadhav (Journal of Environmental Chemical Engineering, 2026)

Sustainable management of whitefly (Bemisia tabaci) in vegetables using entomopathogenic fungi, Isaria farinosa: Characterization, efficacy, insecticide compatibility with molecular docking insights - M. Manjunath; M. H. Kodandaram; Pratap A. Divekar; Vinita Gouri; Suhas G. Karkute; V. Venkataravanappa; A. B. Rai (World Journal of Microbiology and Biotechnology, 2026)

Boosting CO₂ electroreduction via in-situ fabricated CeO₂–MoO₃ heterostructures anchored on activated carbon cloth - Hemavathi Manjunath; Chob Singh; Akshay Gandigawad; Mohd Nor Faiz Norrrahim; Arvind H. Jadhav (Journal of Environmental Chemical Engineering, 2026)

Digital twin-enabled crop yield prediction in semi-arid agriculture: a continuous feedback machine learning framework - Shrikant Malgi; Manjunath M K; Avinash H T (Theoretical and Applied Climatology, 2026)

Unleashing the effect of engineered high-performance S-scheme n–n–n heterojunction g-C3N4/SnO2/Bi2S3 as a dual photo-electrocatalyst for water splitting - Sneha Narayan Kulkarni; Akhila Amasegowda; Hemavathi Manjunath; Arvind H. Jadhav; N.K. Lokanath (Fuel, 2026)

Boosting the photocatalytic efficiency of g-C3N4 for effective removal of RhB and MB from aqueous medium - Mohamed Masri; Girisha K. B; Abdo Hezam; Khaled Alkanad; Talal F. Qahtan; Qasem A. Drmosh; Faten Masri; Kalappa Prashantha; Manjunath S. H; Sanaa Mohammed Abdu Kaid; Udayabhanu; K. Byrappa (Colloids and Surfaces C: Environmental Aspects, 2025)

Unlocking the potential of in-situ thermally reduced graphene oxide anchored with ternary metal oxide-spinel catalyst for sustainable high-performance electrochemical valorisation of CO2 - Sherin Mol C.B; Allwin Sudhakaran; Hemavathi Manjunath; Ashutosh Pandey; Akshaya K. Samal; Mary Nancy T.E; Arvind H. Jadhav (Fuel, 2025)

Spectroscopic Studies of Red Emitting ZrO2:Eu3+ Nanophosphors using Judd−Ofelt Theory for Lighting Applications - H. C. Madhusudhana; C. Manjunath (Journal of Fluorescence, 2025)

Piper betle extract inhibits ferroptosis by scavenging oxyradicals, hydroperoxides and inducing NRF2 regulated antioxidants - Veena Ranganathan; Vidyaranyapura S. Deepashree; Jadeppa Gowda; Sumit K. Dey; Souparnika H. Manjunath; Preethi G. Anantharaju; Durgesh Paresh Bidye; Gurubasavaraj V. Pujar; Vinesh J. Maharaj; Rajesh K. Thimmulappa (Food Bioscience, 2025)

Divergent leaf traits of medicinally important Cocculus hirsutus (L.) Diels- morphoanatomical and molecular authentication - Rakshitha H M. Jain; Y.L. Krishnamurty; K. Manjunath; Shashwathi H S (Ecological Genetics and Genomics, 2025)

Unleashing the potential of N-doped metal-free bi-functional hollow carbon spheres: Catalyst for environmental conservation and advancing sustainable energy solutions - Chob Singh; Hemavathi Manjunath; Allwin Sudhakaran; Omkar B. Bembalge; Rey Eliseo Torrejos; Mohd Nor Faiz Norrrahim; Arvind H. Jadhav (Fuel, 2024)

Structure-based pharmacophore modeling and DFT studies of Indian Ocean-derived red algal compounds as PI3Kα inhibitors - Archana vasuki; H. Jemmy christy; K. Renugadevi; Manjunath Dammalli (Molecular Diversity, 2024)

Seroprevalence and associated risk factors of leptospirosis in bovine dairy farms in Telangana state, India - Sonali Menamvar; Kirubakaran Vinod Kumar; Anusha Alamuri; Enumula Kumar; H. Manjunath Swamy; Gurrappanaidu Govindaraj; Mohandoss Nagalingam; Veeregowda Muniveerappa Belaganahally; Yella Narasimha Reddy; Bibek Ranjan Shome; Vinayagamurthy Balamurugan (Tropical Animal Health and Production, 2023)

Demystifying image-based machine learning: a practical guide to automated analysis of field imagery using modern machine learning tools - Byron T. Belcher; Eliana H. Bower; Benjamin Burford; Maria Rosa Celis; Ashkaan K. Fahimipour; Isabela L. Guevara; Kakani Katija; Zulekha Khokhar; Anjana Manjunath; Samuel Nelson; Simone Olivetti; Eric Orenstein; et al. (Frontiers in Marine Science, 2023)
Image-based machine learning methods are becoming among the most widely-used forms of data analysis across science, technology, engineering, and industry. These methods are powerful because they can rapidly and automatically extract rich contextual and spatial information from images, a process that has historically required a large amount of human labor. A wide range of recent scientific applications have demonstrated the potential of these methods to change how researchers study the ocean. However, despite their promise, machine learning tools are still under-exploited in many domains including species and environmental monitoring, biodiversity surveys, fisheries abundance and size estimation, rare event and species detection, the study of animal behavior, and citizen science. Our objective in this article is to provide an approachable, end-to-end guide to help researchers apply image-based machine learning methods effectively to their own research problems. Using a case study, we describe how to prepare data, train and deploy models, and overcome common issues that can cause models to underperform. Importantly, we discuss how to diagnose problems that can cause poor model performance on new imagery to build robust tools that can vastly accelerate data acquisition in the marine realm. Code to perform analyses is provided at https://github.com/heinsense2/AIO_CaseStudy .

The Spatiotemporal Patterns of Bus Passengers: Visualisation and Evaluation using Non-negative Tensor Decomposition - Nithin K. Shanthappa; Raviraj H. Mulangi; Harsha M. Manjunath (Journal of Geovisualization and Spatial Analysis, 2023)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

2,5-Dimethyl-4-hydroxy-3(2H)-furanone as an Anti-biofilm Agent Against Non-Candida albicans Candida Species - Suganthi Martena Devadas; Usha Y. Nayak; Reema Narayan; Manjunath H. Hande; Mamatha Ballal (Mycopathologia, 2019)

Quantitative Analysis of Phyllanthus Species for Bioactive Molecules Using High-Pressure Liquid Chromatography and Liquid Chromatography–Mass Spectrometry - A. Muthusamy; E. R. Sanjay; H. N. Nagendra Prasad; M. Radhakrishna Rao; B. Manjunath Joshi; S. Padmalatha Rai; K. Satyamoorthy (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

First occurrence of Diaphorina citri in East Africa, characterization of the Ca. Liberibacter species causing huanglongbing (HLB) in Tanzania, and potential further spread of D. citri and HLB in Africa and Europe - Mpoki M. Shimwela; Hossein A. Narouei-Khandan; Susan E. Halbert; Manjunath L. Keremane; Gerald V. Minsavage; Sujan Timilsina; Deogracious Protas Massawe; Jeffrey B. Jones; Ariena H. C. van Bruggen (European Journal of Plant Pathology, 2016)

Host genetic variations in glutathione-S-transferases, superoxide dismutases and catalase genes influence susceptibility to malaria infection in an Indian population - Rayzel C. Fernandes; Marriyah Hasan; Himanshu Gupta; K. Geetha; Padmalatha S. Rai; Manjunath H. Hande; Sydney C. D’Souza; Prabha Adhikari; Angela Brand; Kapaettu Satyamoorthy (Molecular Genetics and Genomics, 2015)

Resistance reaction of gene introgressed lines against rice blast (Pyricularia oryzae) disease - B. Divya; S. Robin; R. Rabindran; H. Manjunath; P. Valarmathi; A. John Joel (Australasian Plant Pathology, 2014)

Synthesis of some novel 1,2,4-triazole and 1,3,4-oxadiazole derivatives of biological interest - Bhimagouda S. Patil; G. Krishnamurthy; M. R. Lokesh; N. D. Shashikumar; H. S. Bhojya Naik; Prashant R. Latthe; Manjunath Ghate (Medicinal Chemistry Research, 2013)

Molecular epidemiology and characterisation of MRSA isolates from Trinidad and Tobago - S. Monecke; H. Nitschke; P. Slickers; R. Ehricht; W. Swanston; M. Manjunath; R. Roberts; P. E. Akpaka (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Involvement of silicon in pearl millet resistance to downy mildew disease and its interplay with cell wall proline/hydroxyproline-rich glycoproteins - S. Deepak; G. Manjunath; S. Manjula; S. Niranjan-Raj; N. P. Geetha; H. S. Shetty (Australasian Plant Pathology, 2008)

Hyperhomocysteinemia: An emerging risk factor for cardiovascular disease - V. Govindaraju; Neelam; C. N. Manjunath; H. Venkataramiah; T. R. Raghu (Indian Journal of Clinical Biochemistry, 2003)

Correlation of histologic types of carcinoma of the uterine cervix and human papillomavirus and herpes simplex virus type 2 DNA sequences in the uterine cervical biopsies - P. Seth; H. Kaur; R. Kaur; K. Verma; N. Manjunath (Archives of Virology, 1988)